Besedilne, pragmatične in medbesedilne žanrotvorne prvine uvodnika - Červ, Gaja (Slavistična revija, 2009)
The article examines the genre features of the journalistic lead in a daily newspaper. The author includes in her textological approach findings of journalistic studies and discourse analysis in the attempt to capture, among other things, the genre features not directly derived from lead editorial texts, but from the communicative circumstances in which these texts are conceived and from inter-textual relations with journalistic discourse.
Keywords: besediloslovje; intertekstualnost; Intertextuality; Journalistic discourse; Journalistic genre; novinarske zvrsti; Text linguistics; uvodnik